2014
DOI: 10.1007/s11102-014-0571-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low dose versus high dose human growth hormone on body composition and lipids in adults with GH deficiency: a meta-analysis of placebo-controlled randomized trials

Abstract: LDs of hGH improve total- and LDL-C, and body composition. Higher doses are more effective on body composition, but not lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
1
15
0
4
Order By: Relevance
“…It is possible that damage to the anterior pituitary resulted in decreased TSH levels and contributed to this weight gain. Growth hormone deficiency has also been associated with weight gain; however, weight redistribution due to altered body composition (increased fat and decreased lean body mass) more accurately describes the long-term effects (66, 67). Alternatively, decreased activity or increased food intake could have contributed to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that damage to the anterior pituitary resulted in decreased TSH levels and contributed to this weight gain. Growth hormone deficiency has also been associated with weight gain; however, weight redistribution due to altered body composition (increased fat and decreased lean body mass) more accurately describes the long-term effects (66, 67). Alternatively, decreased activity or increased food intake could have contributed to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…an arginine test combined with an administration of single dose of GHRH (Growth hormone releasing hormone); L-Dopa and glucagon stimulation tests. The validity of the latter two stimulation tests, is however relative in the literature 36 . Clinical experience has confirmed that lack of 3 pituitary hormones other than GH, implies with almost certainty also complete or at least significant GH deficiency 20 .…”
Section: Dual Use Of Igf-i Measurement In Clinical Practicementioning
confidence: 98%
“…Результати цих досліджень вказують на доцільність використання низьких доз рГР для запобігання зни-женню функції -клітин та подальшого розвитку ЦД 2-го типу у пацієнтів із групи високого ризику [47]. Встановлено, що навіть низькі дози рГР призводять до зниження рівня загального холестерину та ЛПНЩ у дорослих пацієнтів із ДГР [48].…”
Section: № 4(68) • 2015unclassified